2015
DOI: 10.3390/ma8095309
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chitosan/Bacterial Cellulose Composite Films Containing Nanodiamonds as a Potential Flexible Platform for Wound Dressing

Abstract: Chitosan/bacterial cellulose composite films containing diamond nanoparticles (NDs) with potential application as wound dressing are introduced. Microstructural studies show that NDs are uniformly dispersed in the matrix, although slight agglomeration at concentrations above 2 wt % is seen. Fourier transform infrared spectroscopy reveals formation of hydrogen bonds between NDs and the polymer matrix. X-ray diffraction analysis indicates reduced crystallinity of the polymer matrix in the presence of NDs. Approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 59 publications
3
49
0
1
Order By: Relevance
“…[4][5][6] Although ND is emerging as a promising nanomaterial in various areas, a few studies have been performed on the application of ND in topical drug delivery systems. 7,8 One of the main reasons may be poor dispersibility of ND in liquid and semisolid formulations.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Although ND is emerging as a promising nanomaterial in various areas, a few studies have been performed on the application of ND in topical drug delivery systems. 7,8 One of the main reasons may be poor dispersibility of ND in liquid and semisolid formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that the addition of Ch possessing antibacterial properties in culture medium strongly inhibited the A. xylinus growth and BC formation (data not shown). It should be noted that this method could be successful either with application of Ch of a molecular weight not more than 30.000-80.000 Da [19], or upon addition of culture medium plasticizers such as glycerol [9], or use of water soluble Ch, obtained by a special chemical treatment [20]. However, the addition of such forms of Ch during BC synthesis reduced the mechanical properties of cellulose and antibacterial properties of chitosan itself [21].…”
Section: Resultsmentioning
confidence: 99%
“…Upon preparation of antibacterial films cellulose can be combined with several materials to improve antibacterial properties of cellulose. Creation of the antimicrobial wound coverings usually includes addition of antibiotics and antiseptics, different forms of colloid silver and its nanoparticles [8,9]. However, many causative agents of wound infections have multiple resistance to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…MTT assay was performed on MCF-7 cells (10 4 cells per well) in 96-well plate using the previously established method. [52] Briefly, 24 h after plating the cells, they were treated with the samples at concentrations ranging from 1.5 × 10 −6 M to 50 × 10 −6 M. After 44 h, 20 μL of MTT solution (5 mg mL −1 ) was added to the growth medium and the cells were incubated for an additional 4 h. Subsequently, the solution was removed and replaced by 200 μL of dimethyl sulfoxide (DMSO) to solubilize formazan blue crystals. Absorption was read on multiwell plate reader machine (BioTek Synergy HT, US) using the standard wavelengths of 592 nm.…”
Section: Methodsmentioning
confidence: 99%